THE INFLUENCE OF ISLAMIC ENTREPRENEURSHIP TOWARDS THE ORGANIZATION PERFORMANCE THROUGH ORGANIZATION COMMITMENT IN MA’SOEM GROUP - Yudhy Yudhy (Univeristas Islam Bandung, 2021)
The purpose of this research is to discuss the influence of Islamic entrepreneurship towards the organization performance through organization commitment. The object of this research is the unit leader and division leader in Ma’soem Group. The appropriate sample used has been randomly chosen by probability sampling method with 118 respondents. Data analysis is conducted using Structural Equation Modeling (SEM). The result of research shows that Islamic entrepreneurship is affecting the organization performance, and the organization commitment do not affect the organization performance. For indirect influence, organization commitment cannot mediate the influence of Islamic entrepreneurship towards organization performance.